Rancang Bangun Mesin Penggulung Lilitan Kawat Transformator Otomatis Berbasis Arduino Uno - Denny Irfan; Junaidi Junaidi; Arif Surtono (Journal of Energy, Material, and Instrumentation Technology, 2021)
Research on application of the design an Arduino Uno-based automatic transformer wire winding machine has been carried out. The research aim was to make an automatic winding machine using wire coils that can be adjusted for rotation speed and high accuracy of the number of turns. In testing system, the enamel wire was wrapped around with a different number of turns, that is 200;400;600;800;1000 turns. The calibration method in this study was carried out manually, that is recounting the turns on the koker that had been wrapped using an automatic winding machine. The speed of the winding machine is calibrated using a tachometer. The results of the calculation of the average rolling accuracy of 99,73%.